The Formulation of Social Neuroscience Midlife Crisis Predictability Apparatus for Midlife Progression - Boey, Loh Hock (Integrated Journal for Research in Arts and Humanities, 2022)
The purpose of this paper is studying the social brain in the context of neuroscience to unveil their intricate relationship between social environment and neuroscience responses by formulating an effective social neuroscience midlife crisis apparatus to help creating predictability of this phenomenal by preventing it from the earlier stage. The research design was taking a three fundamental levels. The foundational level to collect data from 32 middle aged homogeneous sampling of midlife crisis sufferers through qualitative content analysis design for social and neuroscience thematic by conducting an in depth interview. The verification level to guarantee the validity of the data collected through the selected tests for reaching the re-tested reliability data. The confirmatory level to administer the data through the quantitative survey methods by using self-portrayed midlife crisis experience and self-reported midlife crisis definition to investigate the causal relationship of social and neuroscience to reach an outcome, thereafter the outcome is compared with verified qualitative social neuroscience midlife crisis. Data were analysed by SPSS/Version 25 for principal components analysis. Results from N=32 focus group shows 3 social construct components with 10 neuro-response delineating to 45 unit of meaning of social neuroscience factors. The literature and focus study of total 79 combined factors under Tucker's congruence coefficient interpretation shows the desirable 44 social neuroscience factors in 3 components emerged as independent identity factors. Six midlife crisis expert of different field respondents’ validation by content validity index (CVI=0,906 value) has confirmed that the content is suitable to be used as the measurement for social-neuroscience midlife crisis. Pilot study N=34 analysis by content validity ratio (CVR=0.529 to 1) where 38 social neuroscience factors is retained and tested for internal consistency by communalities=0.5 results that all 38 items are relevant. Data comparison confirmatory by triangle test analysis in which Pearson correlation coefficient (r= > 0.75) shows a positive strong relationship between two sets of variables. The results conclude that there are 3 components, namely biological life faded moment, interior misery intensity and personal hibernating symptom with 38 social neuroscience factors in the predictability apparatus that influence midlife crisis and should be used as predicting and developing therapeutic intervention facility to conquer the midlife crisis. Contribution of Social neuroscience midlife crisis apparatus is an effective scaled system for early prediction and prevention to diminish midlife crisis rate of occurrence, ultimately the details unit of meaning crisis predictability factors scale to assure the accurate intervention devising instrument to social support services.